PENGARUH REPUTASI KAP, AUDIT REPORT LAG, DAN LEVERAGE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Sektor Consumer Cyclical yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2022) - Al Vito, Muhammad; Laksito, Herry (Diponegoro Journal of Accounting, 2024)
A going concern audit opinion is a part of the auditor’s independence report that added when the auditor has doubts about company’s ability to maintain the going concern of business. This research aims to examine the effect of reputation of audit firm and audit report lag, also leverage against going concern audit opinion. The variable used in this research is reputation of audit firm, audit report lag, and leverage as independent variables, while going concern audit opinion as dependent variable.Research objects are consumer cyclical sector companies listed on Indonesia Stock Exchange within 2021-2022. Sample tested in this study obtained using purposive sampling method with certain criteria. The analytical method used in this research is logistic regression analysis using SPSS 25.The research results stated that reputation of audit firm has no significant effect on going concern audit opinion. Audit report lag has no significant effect on going concern audit opinion. Leverage has positive and significant effect on going concern audit opinion.